The supernatural society - Ogle, Rex (Inkyard Press, 2022)
After moving from New York City to the small town of East Emerson, Will Hunter realizes he's the only one who can see the monsters roaming around. When his dog Fitz goes missing, along with all the other pets in town, Will teams up with outcasts Ivy and Linus to find them and uncover the truth about the town's eerie happenings.